Assessing the feasibility of parent participation in a commercial weight loss program to improve child body mass index and weight-related health behaviors. (September 2018) - Song, MinKyoung; Lee, Christopher S; Lyons, Karen S; Stoyles, Sydnee; Winters-Stone, Kerri M
Objectives: Little is known about how children's health might be affected by parents' participation in commercial weight loss programs. Given that more than 3.2 million people subscribe to just one commercial weight loss program, Weight Watchers, any secondary effects on children's weight-related health behaviors (e.g. dietary behaviors, physical activity, and sedentary time) and body mass index from parent participation in commercial weight loss programs may have significant public health implications. This study examined the feasibility of conducting a study to assess such effects. Methods for recruitment and retention, and perceived acceptability and satisfaction among participants in small-scale preliminary study, were evaluated. Changes in body mass index and health behaviors among the parent–child dyads were also measured to test whether a larger-scale study would be warranted. Methods: This was an 8-week, pre–post observational feasibility study involving 20 parent–child dyads where both members had overweight or obesity. Physical and behavioral data were collected at baseline and 8 weeks from both members of the dyads. Parenting data were collected at the same time periods through parents' self-report. Bivariate correlation was used to quantify the associations in changes for dyad members. Results: Feasibility goals for retention and perceived acceptability/satisfaction among participants were met. We reached approximately 80% of our enrollment goal. Parents showed a significant decrease in body mass index of 0.53 points (p < 0.05), while children showed a significant increase in raw body mass index (0.42, p < 0.05) and body mass index percentile (0.59, p < 0.05). However, correlation between changes in parent body mass index and changes in children body mass index percentile was positively correlated (r = 0.24, p = 0.31). A decrease in parent intake of total fat was associated with a decrease in the intake of fat in their children (r = 0.47, p < 0.05). Conclusion: Our findings support the viability of a larger-scale follow-up to assess the potential of using parent-only commercial weight loss program as a mechanism for improving health behaviors and body mass index in children with overweight or obesity.